2014
DOI: 10.1007/s10964-014-0158-z
|View full text |Cite
|
Sign up to set email alerts
|

The Age–IPV Curve: Changes in the Perpetration of Intimate Partner Violence During Adolescence and Young Adulthood

Abstract: Research on intimate partner violence (IPV) has evolved over the last decade with increasing interest in how IPV develops over adolescence and young adulthood. Studies examining patterns of IPV over time have generally focused on victimization with less attention to temporal shifts in perpetration. While it is generally assumed that IPV peaks during young adulthood, this has not been empirically verified and documented. Additionally, prior longitudinal analyses of IPV have focused on identifying trajectories a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
159
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(196 citation statements)
references
References 113 publications
25
159
1
5
Order By: Relevance
“…This gap is critical because emerging adulthood is an important developmental period when romantic relationships are taking shape and interpersonal patterns are forming (Arnett 2000;Shulman and Connolly 2013;Zarrett and Eccles 2006). Intimate partner violence is known to peak in emerging adulthood, yet this phenomenon during an important developmental period remains largely understudied and warrants more research (Capaldi and Kim 2007;Johnson et al 2015;O'Leary 1999;Unger et al 2014). Our research addresses a gap in previous studies by providing a better understanding of the associations of acculturation, traditional gender role attitudes, substance use, and depressive symptoms in adolescence with both intimate partner violence perpetration and victimization in emerging adulthood among Latinos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gap is critical because emerging adulthood is an important developmental period when romantic relationships are taking shape and interpersonal patterns are forming (Arnett 2000;Shulman and Connolly 2013;Zarrett and Eccles 2006). Intimate partner violence is known to peak in emerging adulthood, yet this phenomenon during an important developmental period remains largely understudied and warrants more research (Capaldi and Kim 2007;Johnson et al 2015;O'Leary 1999;Unger et al 2014). Our research addresses a gap in previous studies by providing a better understanding of the associations of acculturation, traditional gender role attitudes, substance use, and depressive symptoms in adolescence with both intimate partner violence perpetration and victimization in emerging adulthood among Latinos.…”
Section: Discussionmentioning
confidence: 99%
“…Early romantic relationship patterns during this period can be precursors to interpersonal relationships later in life (Collins et al 2009;Zarrett and Eccles 2006). Intimate partner violence perpetration peaks in emerging adulthood at age 25 in the general population (Johnson et al 2015;O'Leary 1999). Intimate partner violence perpetration and victimization among young men and women are known to co-occur, with each individual acting as perpetrator and victim on different occasions (Dardis et al 2015).…”
Section: Gender Age and Bidirectional Violencementioning
confidence: 99%
“…What is unclear however, despite the small number of longitudinal studies available is whether, akin to delinquency (e.g., Moffitt, 1993), those who initiate violence and abuse at an earlier age, are more likely to engage in more severe forms during adulthood that are characterized by coercive control. A recent examination of the age-crime and age-IPV violence curves using an accelerated longitudinal design from ages 13 to 28 (Johnson, Giordano, Manning, & Longmore, 2014) showed that for boys, the two curves mirrored each other in terms of their shape, with the peak of both delinquency and physical IPV occurring between the ages of 17 and 20, although more boys were involved in delinquency (33%) than IPV (20%). It was found that IPV in males shared risk factors with delinquency (antisocial behavior, drug and alcohol use), and that these variables accounted for 22% of the age-related difference in IPV.…”
Section: Developmental and Family Of Origin Influencesmentioning
confidence: 99%
“…Rates of violence between partners tend to increase between ages 15 and 25, reaching the peak between ages 20 and 25 (Johnson et al, 2014;O'Leary, 1999). This period typically corresponds with attendance in college, which has been shown to be a time of increased risk for dating violence (Kaukinen, 2014;Smith et al, 2003).…”
mentioning
confidence: 99%